Penggunaan Media Daring Dalam Pelatihan Kader Tanggap Bencana - Eka Rudy Purwana; I Gusti Ayu Sri Puja Warnis Wijayanti; Sitti Rusdianah Jafar; Zulkifli Zulkifli (Poltekkes Kemenkes Mataram, 2022)
Crisis management efforts due to disasters are a series of activities that began before the occurrence of outbreaks and disasters carried out through prevention, mitigation (softening / taming impacts) and preparedness in the face of epidemics and disasters. Activities carried out during outbreaks and disasters are in the form of emergency response activities and then after the outbreak and disaster in the form of recovery/rehabilitation and reconstruction activities. Negeri 8 Mataram with online media. This study uses a quasi-experimental design with one pre and post test design. A total of 40 Disaster Response Cadre cadres (KATANA) were given training for disaster response cadres and measured disaster preparedness before and after training with online media. Data analysis using paired t test. The results show that there is an effect of disaster response training on disaster preparedness with a p value of 0.000 <0.05. Conclusion, The results of this study are expected to be an innovation program for youth cadres to improve disaster preparedness.